Tourists' Perceptions of Local Street Food: Angkringan, Yogyakarta's Culinary Icon - Suci Sandi Wachyuni; Kadek Wiweka (International Journal of Travel, Hospitality and Events, 2022)
Purpose: Angkringan is one of the culinary icons of Yogyakarta which is famous for its being street food. With the development of Yogyakarta's culinary as a tourist attraction, the purpose of this study is to determine tourists' perceptions of Angkringan. Research methods: This study employs a quantitative approach, with a survey conducted via WhatsApp broadcast messages. Purposive sampling was used, and the sample size was 100 respondents. The data analysis method applied is quantitative descriptive statistics,. Results and discussion: Angkringan in Yogyakarta is well-liked by tourists. Food quality has the highest average value, followed by portions, promotions, menu variations, service quality, and prices in a certain order. The last three indicators, that is cleanliness, taste, and atmosphere, all share the same average value. Implication: Understanding how tourists perceive Angkringan can provide suggestions for the development of community Angkringan businesses, particularly in Yogyakarta, this research has theoretical and practical implications. Keywords: angkringan, culinary, street food, local food, perception.